Nikolaj von Wassilko. Bukovinian statesman and diplomat - Dobrzhanskiy, Oleksander (Stefan cel Mare University of Suceava, 2019)
The article is dedicated to the study of the political biography of Nikolaj von Wassilko, a well-known Bukovinian leader, one of the most controversial personages among Ukrainian politicians of Austria-Hungary at the end of the 19 th – the beginning of the 20 th century. It is worth mentioning that many scientists from various countries wrote about N. Wassilko, but separate studies about his life and political activities have not been written yet. Author paid considerable attention to the formation of N. Wassilko's political views, the evolution of his preferences from conservative Rusynism and Moscophilia philosophy to the populistic doctrine. Since the beginning of the 20th century, N. Wassilko became almost the sole leader of Ukrainians in Bukovina. The article presents the analysis of his activities in the Austrian Parliament, the Diet of Bukovina, public organizations, and his initiatives to resolve various regional issues. His activities in the years of World War I were equally rich. In particular, the article shows his diplomatic activities as the ambassador of the ZUNR (West Ukrainian People's Republic) in Vienna, the ambassador of the UPR (Ukrainian People's Republic) in Switzerland and other countries. At the end of the research, the author points out the remarkable path of N. Wassilko in the history of the Ukrainian movement in Bukovina in the early twentieth century, as one of the central figures of the Ukrainian diplomacy during 1918-1924.
Keywords: N. Wassilko, S. Smal-Stotsky, Bukovina, Austria-Hungary, Ukrainian People's Republic, World War I, Austrian Parliament, The Diet of Bukovina.